Hydrothermal Synthesis and Crystal Structure of Cd(II) Coordination Polymer - Xing, Jianxin (Asian Journal of Chemistry, 2010)
By hydrothermal method, the compound [Cd(nia)2(H2O)]n (nia = nicotinate) was synthesized and its structure was characterized with elemental analysis and X-ray diffractometer. The crystal is orthorhombic, space group Pbca with a =11.458(s), b = 12.113(2), c = 17.435(3) Å, a =b = g =90°, Mr = 374.62, V = 2419.8(7)Å3, Dc = 2.057 g/cm3, F(000) = 1472 and Z = 8. The Cd(II) center adopt a distorted octahedron geometry which is surrounded by 6 coordination atoms from nicotinate and water molecule.